AMINO ACID REMOVAL DURING HEMODIALYSIS OF PATI-ENTS WHO HAD UNDERGONE INTRADIALYTIC PAR-ENTERAL NUTRITION. - Norio Hanafusa; Yoshifumi Hamasaki; Kosuke Negishi; Eisei Noiri; Toshiro Fujita (The Korean Society of Nephrology, 2012)
Hemodialysis removes solutes uniformly according to their molecular weight. During each hemodialysis session, 6-8 g of amino acids are reportedly removed into the dialysate. Little is known about the amount of amino acids removed from those who have undergone intradialytic parenteral nutrition (IDPN). Objective: We measured amino acid amounts prospectively during hemodialysis treatment. Methods: We used 200 ml of 7.2% amino acid solution (KidminTM), 200 ml of 50% glucose, and 20% of lipid emulsion as IDPN fluid. Blood samples were collected at the beginning and end of each session. The dialysate portion was also collected. Results: Six patients were included in this study after providing written informed consent. The amount of amino acids removed during hemodialysis sessions was calculated as 9.1±1.4 g, which was less than that infused as IDPN. The profiles of the removed amino acids showed that the amount removed was less than that within IDPN. However, for tyrosine and alanine, hemodialysis treatment removed more amino acids than that infused as IDPN, as well as amino acids that were not IDPN solution constituents. During a 2-week follow-up period, no significant change in amino acid profiles was observed. Conclusions: IDPN entirely supplemented the removed amino acids, although some amino acids were not restored.